Cataract surgery in patients with diabetes mellitus. Prevention and optimisation of the diabetic macular edema therapy - A. Zh. Fursova; A. S. Derbeneva; M. A. Vasilyeva; Yu. A. Gamza; P. N. Pozdnyakova; F. K. Rabota (Российский офтальмологический журнал)
Diabetes mellitus (DM) is a major public health problem, with approximately one third having signs of diabetic retinopathy (DR). In such patients, cataracts develop at an earlier age and 2–5 times more frequently. The incidence of macular edema (ME) after phacoemulsification of cataracts (FEC) in patients with diabetes has been shown to increase by 1.80 times and, in the presence of DR by 6.23. The critical period for retinal deterioration is 2 months after FEC, which requires an active therapy and monitoring. For patients with pre-existing diabetic macular edema (DME), If the cataract does not affect daily activities of patients with a pre-existing DME and the optical clarity is adequate, it is preferable to postpone surgical treatment in order to maximize retinal stabilization on OCT at two consecutive visits with a month’s interval between. In the case of severe impairment of lens transparency, FEC with an intravitreal injection of anti-VEGF 28 days or steroids 1 month before surgery under strict monitoring of the retinal condition using OCT is recommended. If macular changes are absent and there is a risk of developing DME, the use of nonsteroid anti-inflammatory drugs is necessary. Prophylactic intravitreal therapy is unacceptable in the absence of MO.